The nucleotide sequence at the transcription termination site of ribosomal RNA in Drosophila melanogaster. - Mandal, R K (1981)
The sequence of 300 nucleotides surrounding the transcription termination site for ribosomal RNA in Drosophila melanogaster has been determined. The precise position of the RNA 3'-end was located by sizing rDNA fragments protected from S1 nuclease by hybridization with cytoplasmic 28S rRNA or with nuclear 38S pre-rRNA. Next, the sequence of the first 10 nucleotides at the 3'-end of 28S and 38S rRNA was determined directly. The results indicate the absence of 3'-terminal processing of the 38S pre-rRNA. The nucleotide sequence from a position 27 nucleotides upstream to 150 nucleotides downstream from the termination site was identical in three uninterrupted rRNA genes and one interrupted gene, except for a single base change in the spacer region of one clone. The terminal 100 nucleotides of Drosophila 28S rRNA have more than 60 per cent homology with the corresponding region of Xenopus 28S rRNA and yeast 26S rRNA.